The Implementation of Online Learning in Early Childhood Education During the Covid-19 Pandemic - Muhdi; Nurkolis; Yuliejantiningsih, Yovitha (Jurnal Pendidikan Usia Dini, 2020)
Covid-19 has changed the learning process from class attendance to distance learning using the Internet. Early childhood education is threatened to enter into the lost generation, due to distance learning, which causes confusion for teachers and parents to be able to provide the best stimulation for them. Therefore, the Indonesian government made a new policy on online learning. The objectives of this research are to find how effective at online learning policy formulation, how productive it is in policy implementation, and what are the obstacles of the implementation at Early-Childhood Education (ECE). This qualitative research uses a mixed method approach with an iterative analysis design, conducted in Central Java Province in 35 districts / cities with 1,899 respondents. Data collection techniques with open-closed questionnaires, study from 15 documentation, and in-depth interviews. Data analysis uses quantitative-qualitative software Nvivo12+, with Miles and Huberman models. The results showed the policy formulation of online learning at ECE has been effective. However, the implementation of online learning policy at ECE still takes a lot of effort to become more powerful in preventing a decline in learning. There are five obstacles in in applying this in the field, namely the ability of teachers, the ability of parents, economic capability, facility constraints, and pedagogical constraints. Keywords: Online Learning Policy; Children Engagement; Learning Management System References Allen, I. E., Seaman, J. (2013). Changing course: Ten years of tracking online education in the United States. ERIC, ISBN 0984028838. Asilestari, P. (2016). Komputer Interaktif sebagai Media Pengajaran Bahasa Inggris pada Anak Usia Dini. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 2, n. 1, p. 55-62. Association, I. I. S. P. (2018). Penetrasi & Profil Perialku Pengguna Internet Indonesia. Coates, H. (2006). Student engagement in campus-based and online education: University connections. Routledge, ISBN 1134161530. Ha, Young. & Im, Hyunjoo. (2020). The Role of an Interactive Visual Learning Tool and its Personalizability in Online Learning: Flow Experience. Online Learning, 24, n. 1. Harjanto, T. & Sumunar, D. S. E. W. (2018). Tantangan Dan Peluang Pembelajaran Dalam Jaringan: Studi Kasus Implementas Elok (E-Learning: Open For Knowledge Sharing) Pada Mahasiswa Profesi Ners. Jurnal Keperawatan Respati Yogyakarta, 5, p. 24-28. Imron, A. (1995). Kebijaksanaan pendidikan di Indonesia: Proses, produk dan masa depannya. Bumi Aksara, ISBN 9795262319. Inoue, Y. (2007). Online education for lifelong learning. IGI Global, ISBN 1599043211. Irma, C. N., Nisa, K. & Sururiyah, S. K. (2019). Keterlibatan Orang Tua dalam Pendidikan Anak Usia Dini di TK Masyithoh 1 Purworejo. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 3, n. 1, p. 214-224. Jebba, A. M. & Umaru, N. N. (2019). The role of social media in reshaping the academic activities of vocational and technical education lecturers in Nigeria. Int. J. Eval. & Res. Educ. Vol, 8, n. 4, p. 735-741. Johnson, K. & Manning, S. (2010). Online education for dummies. Canada: John Wiley & Sons Publishing ISBN 0470536209. Juwah, C. (2006). Interactions in online education: Implications for theory and practice. Routledge, ISBN 1134247494. Kemendikbud. (2020). Surat Edaran Nomor 4 Tahun 2020 Tentang Pelaksanaan Kebijakan Pendidikan Dalam Masa Darurat Penyebaran Corona Virus Disease (Covid-19). Kong, S. C., Chan, T.-W., Griffin, P. & Hoppe, U. et al. (2014). E-learning in school education in the coming 10 years for developing 21st century skills: Critical research issues and policy implications. Journal of Educational Technology & Society, 17, n. 1, p. 70-78. Kwon, J. B., Debruler, K. & Kennedy, K. (2019). A Snapshot of Successful K-12 Online Learning: Focused on the 2015-16 Academic Year in Michigan. Journal of Online Learning Research, 5, n. 2, p. 199-225. Layne, M., Boston, W. E. & Ice, P. (2013). A longitudinal study of online learners: Shoppers, swirlers, stoppers, and succeeders as a function of demographic characteristics. Online Journal of Distance Learning Administration, 16, n. 2, p. 1-12. Lynch, M. M. (2002). The online educator: A guide to creating the virtual classroom. Routledge, ISBN 1134542542. Novianti, R. & Garzia, M. (2020). Penggunaan Gadget Pada Anak; Tantangan Baru Orang Tua Milenial. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 4, n. 2. Nugroho, R. (2008). Kebijakan Pendidikan: Pengantar untuk Memahami Kebijakan Pendidikan Sebagai Kebijakan Publik. Yogyakarta: Pustaka Pelajar. Nugroho, R. (2017). Public Policy: Dinamika Kebijakan, Analisis Kebijakan, dan Manajemen Politik Kebijakan Publik. Jakarta: Elex Media Komputindo. Palloff, R. M. & Pratt, K. (2002). Lessons from the cyberspace classroom: The realities of online teaching. California: John Wiley & Sons Publishing, ISBN 0787959960. Pangondian, R. A., Santosa, P. I. & Nugroho, E. (2019). Faktor-Faktor Yang Mempengaruhi Kesuksesan Pembelajaran Daring Dalam Revolusi Industri 4.0. Panjaitan, N. Q.; Yetti, E. & Nurani, Y. (2020). Pengaruh Media Pembelajaran Digital Animasi dan Kepercayaan Diri terhadap Hasil Belajar Pendidikan Agama Islam Anak. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 4, n. 2, p. 588-596. Pebriana, P. H. (2017). Analisis penggunaan gadget terhadap kemampuan interaksi sosial pada anak usia dini. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 1, n. 1, p. 1-11. Pertiwi, W. K. (2020). Penetrasi Internet di Indonesia Capai 64 Persen. https://tekno.kompas.com/read/2020/02/20/14090017/penetrasi-internet-di-indonesia-capai-64-persen. Ramadhan, B. (2020). Ini Data Pengguna Internet Di Seluruh Dunia Tahun 2020. Jakarta https://teknoia.com/data-pengguna-internet-dunia-ac03abc7476. Roach, V. & Lemasters, L. (2006). Satisfaction with online learning: A comparative descriptive study. Journal of Interactive Online Learning, 5, n. 3, p. 317-332. Rohita, R. (2020). The Ability of Ece Teachers to Use ICT in The Industrial Revolution 4.0. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 4, n. 2, p. 502-511. Rostaminezhad, M., Mozayani, N., Norozi, D. & Iziy, M. (2013). Factors related to e-learner dropout: Case study of IUST elearning center. Procedia-Social and Behavioral Sciences, 83, p. 522-527. Sari, K. M. & Setiawan, H. (2020). Kompetensi Pedagogik Guru dalam Melaksanakan Penilaian Pembelajaran Anak Usia Dini. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 4, n. 2, p. 900-912. Seok, S. & Dacosta, B. (2020). Relationships Between Young South Koreans’ Online Activities and Their Risk of Exploitation. Journal of Online Learning Research, 6, n. 1, p. 77-101. Setyaji, A., Iskak, A., Sukmaningrum, R. & Hawa, F. (2015). Komputer Interaktif Sebagai Media Pengajaran Bahasa Inggris Pada Anak Usia Dini. E-Dimas: Jurnal Pengabdian kepada Masyarakat, 6, n. 1, p. 1-12. Sharoff, L. (2019). Creative and Innovative Online Teaching Strategies: Facilitation for Active Participation. Journal of Educators Online, 16, n. 2, p. n2. Suhartanto, H. (2010). Survei 2009: Mutu Situs E-Learning Sekolah Indonesia Masih Sangat Minim. Jurnal Sistem Informasi,6, n. 1, p. 80-83. Sum, T. A. & Taran, E. G. M. (2020). Kompetensi Pedagogik Guru PAUD dalam Perencanaan dan Pelaksanaan Pembelajaran. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 4, n. 2. Swan, K. (2003). Learning effectiveness online: What the research tells us. p.13-47. Taufik, A., Apendi, T., Saidi, S. & Istiarsono, Z. (2019). Parental Perspectives on the Excellence of Computer Learning Media in Early Childhood Education. Jurnal Pendidikan Usia Dini, 13, n. 2, p. 356-370. Tilaar, H.; Nugroho, R. (2009). Kebijakan Pendidikan: Pengantar untuk Memahami Kebijakan Pendidikan dan Kebijakan Pendidikan sebagai Kebijakan Publik. Yogyakarta: Pustaka Pelajar. Ulya, S. I. (2019). Analisis Penggunaan Gedget Terhadap Kemampuan Interaksi Sosial Dan Komunikasi Pada Anak Usia Dini. 89-96. Vonderwell, S. & Zachariah, S. (2005). Factors that influence participation in online learning. Journal of Research on Technology in education, 38, n. 2, p. 213-230. Wang, Q., Zhu, Z., Chen, L. & Yan, H. (2009). E‐learning in China. Campus-Wide Information Systems. Winter, J., Cotton, D., Gavin, J. & Yorke, J. D. (2010). Effective e-learning? Multi-tasking, distractions and boundary management by graduate students in an online environment. ALT-J, 18, n. 1, p. 71-83. Yu, E. (2020). Student-Inspired Optimal Design of Online Learning for Generation Z. Journal of Educators Online, 17, n. 1, p. n1. Zaini, M. & Soenarto, S. (2019). Persepsi Orangtua terhadap Hadirnya Era Teknologi Digital di Kalangan Anak Usia Dini. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini, 3, n. 1, p. 254-264.